Solving Segment Routing Problems with Hybrid Constraint Programming Techniques - Hartert, Renaud; Schaus, Pierre; Vissicchio, Stefano; Bonaventure, Olivier (Lecture notes in computer science, 2015)
Segment routing is an emerging network technology that exploits the existence of several paths between a source and a destination to spread the traffic in a simple and elegant way. The major commercial network vendors already support segment routing, and several Internet actors are ready to use segment routing in their network. Unfortunately, by changing the way paths are computed, segment routing poses new optimization problems which cannot be addressed with previous research contributions. In this paper, we propose a new hybrid constraint programming framework to solve traffic engineering problems in segment routing. We introduce a new representation of path variables which can be seen as a lightweight relaxation of usual representations. We show how to define and implement fast propagators on these new variables while reducing the memory impact of classical traffic engineering models. The efficiency of our approach is confirmed by experiments on real and artificial networks of big Internet actors.